Water desalination system using solar heat: A review. (January 2017) - M, Chandrashekara; Yadav, Avadhesh
Abstract: Most of the desalination systems are energy intensive, which consume high grade energy like gas, electricity, oil and fossil fuels. These processes lead to carbon footprints, which causes depletion of ozone layer as well as health hazards on mankind. It is also lead to global warming which is the burning topic and becomes threat to life sustainability. The potential of harnessing solar energy is most efficient and effective for heat to heat conversion. The thermal desalination is a low temperature application processes with one time investment for life time water production up to 10 to 15 years. In this paper, various solar thermal desalination methods such as direct and indirect methods have been discussed. The indirect methods are preferable for medium and large scale desalination systems, whereas the direct methods employing the solar stills are more suitable for small scale systems. The performance of the low cost solar stills can be improved with simple modification by using various locally available materials. These low cost stills can be easily and economically fabricated for meeting daily need of the fresh drinking water. These low cost solar stills are sufficient for the small households and communities living in islands, coastal areas. It can also be uses for distillation of brackish water for the population residing near river banks. Such a system also suitable for the fluoride affected area to remove fluoride from the water. The low cost solar stills are sufficient for removal of arsenic, mercury, cadmium, coliform, virus and bacteria.